Concordance between referral and final diagnoses of pediatric patients with vascular malformations - Elena Pastrana-Arellano; Sofía Valdés-Loperena; Yaneli Vargas-Flores; Carola Durán-McKinster; María T. García-Romero (Permanyer, 2023)
Background: Vascular malformations (VaM) are a heterogeneous group of disorders resulting from the dysmorphogenesis of blood vessels. Although correct classification is relevant to providing adequate treatment according to evidence-based medicine, diagnostic terminology may be misused or need clarification. Methods: We conducted a retrospective study to measure agreement and concordance between referral and final confirmed diagnoses of 435 pediatric patients with VaM newly referred to the multidisciplinary Vascular Anomalies Clinic (VAC) using Fleiss kappa (κ) concordance analysis. Results: We found fair concordance between referral and confirmed diagnoses of VaM (κ 0.306, p < 0.001). Lymphatic malformations (LM) and VaM associated with other anomalies showed moderate diagnostic concordance (κ 0.593, p < 0.001 and κ 0.469, p < 0.001, respectively). Conclusions: Continuing medical education strategies are required to improve physician knowledge and diagnostic accuracy in patients with VaM.